Effects of film thickness and alkaline concentration on dissolution kinetics of poly(4-hydroxystyrene) in alkaline aqueous solution. (1st June 2022) - Tanaka, Naoki; Matsuoka, Kyoko; Kozawa, Takahiro; Ikeda, Takuya; Komuro, Yoshitaka; Kawana, Daisuke
Abstract: The dissolution behavior of a simple combination of poly(4-hydroxystyrene) films and tetramethylammonium hydroxide aqueous solution was analyzed to gain a fundamental understanding of the effects of film thickness and alkaline concentration on the dissolution kinetics of chemically amplified resists. Films of four different thicknesses, from thick (approximately 900 nm) to thin (approximately 50 nm), were developed in 22 different developers of different concentrations. The dissolution behavior of each combination was observed using a quartz crystal microbalance. Differences in dissolution kinetics due to film thickness were observed even between relatively thick films such as 900 and 500 nm thick films in dilute developers. These differences were considered to be caused by the diffusion of the solution into the films. Thin films also showed characteristic behavior with dilution. This behavior was due to the interaction between the substrate and the films, unlike in the case of thick films.